The Potential of Hydroponics as a Solution for Food Security and Economics Resilience: Issues and Challenges of Smart-Agriculture - Rendi Zulni Ekaputri; Dewi Jumiarni; Berto Usman; Bhakti Karyadi; Erik Perdana Putra (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2021)
Skills improvement is in line with efforts to tackle food security during the COvid-19 pandemic. This effort can be done by using hydroponic techniques. This community service aims to increase the knowledge and skills of the Sint Carolus Junior High School residents in Bengkulu City in utilizing hydroponic technology. The method of activities provided includes training, supervised assignment, monitoring and evaluation. Activities were held on August 21, 2020 and August 28, 2020 at Sint Carolus Middle School, Bengkulu. Based on the activities that have been carried out, it can be concluded that community service activities in hydroponic technology training (models) get a very good response in terms of the material, methods and partner satisfaction. Hydroponic technology training model has increased the knowledge and skills of Sint Carolus Middle School residents in Bengkulu City, particularly by using the styrofoam box waste as a medium for plant planting.